Optical interaction in active analog circuit elements. (September 2017) - Vogt, I.; Nakamura, T.; Boit, C.
Abstract: This publication introduces (spectral) photon emission (PEM) and electro-optical frequency mapping (EOFM/LVI) measurements to analog circuit elements (simple, cascode and low-voltage current mirrors). Different operating conditions of the devices are probed and the voltage dependence of the signals is analyzed. Results partly show close similarities to optical probing of digital IC's, but also differences in voltage dependence and signal levels due to more complicated voltage and signal distributions along the devices. Highlights: PEM operating conditions on simple current mirror possible PEM on cascode, low-voltage current mirror not possible due to voltage distribution along several FETs in series Electron temperatures for simple current mirror between 750 and 1400 K EOFM slopes on simple, cascode and low-voltage current mirror show strong linear rise for higher voltages. Only weak EOFM signals below threshold voltage